Body image in fertile and infertile women - SJ Younesi; A Salagegheh (JRI, 2001)
Various studies show that infertility treatment in addition to physical involvement, cause undesirable psychological reactions. One of these cases is disorder and change in mental body image. This research is a case control study with aim of determination of mental image of fertile and infertile women referring to health and infertility treatment centers selected in Tehran city in year of 2000. Observed persons were divided as group of women with fertility problems (test group) and group of fertile women (control group). In this research, subjects as two groups of fertile and infertile were chosen from 5 Health centers namely: Panzdah Khordad, Hospitals of Shariati, Mirza Koochak Khan, Day and Saram Medical Center according to purposeful sampling. There were 100 persons in each group. Procedure of data gathering was with help of query form questionnaire of mental image of body, which was prepared with general construct procedure. This has been called mental structures list in Iran. Qualified fertile and infertile women were chosen from mentioned centers. A primary conversation was done with them regarding goals and ways of research. After their agreement, questionnaires were given to them. Then, considering score of each question, answers of fertile and infertile women were assessed and results were compared with help of statistical analysis methods. Information showed that studied mental image of fertile and infertile women were different from each other. In various elements of mental image (active body in isolation, real body, body in way which people see it, body in way which husband sees and knows it and body the way which family of husband see and know it), two groups had meaningful statistical differences (P<0.05). This means infertile women showed some degrees of mental image disorder. Self or body mental image can cause anxiety and depression. In this regard methods and behavioral techniques can control theses signs up great degrees.
Keywords: Body image disorder, Body image, Infertile women, Mental construct, Appearance, Competence